Eudendrium rugosum Fraser 1940 ... - Calder, Dale R.; Choong, Henry H. C. (Zenodo, 2018)
Eudendrium rugosum Fraser, 1940a Eudendrium rugosum Fraser, 1940a: 575, pl. 32, fig. 1. Holotype. USNM 43433: North Atlantic Ocean, Flemish Cap, R / V Albatross Sta. 2693, 46°53’N, 44°39’30”W, 11 August 1886, large beam trawl, 143 m, two larger and a few smaller fragments of a colony, with hydrocauli up to 1.3 cm high, without hydranths but with a few male gonophores, labelled “ type ”; ethanol. Paratype. BCPM 976-00250-001: North Atlantic Ocean, 46°53’N, 44°39’30”W, 11 August 1886, 139 m, several colony fragments, up to 5 mm high, in very poor condition, gonophores not seen, labelled "co-type"; 60% IPA. Type locality. International waters: North Atlantic Ocean, Flemish Cap, 46°53’N, 44°39’30”W (Fraser 1940a). Current status. Valid. Remarks. Fraser (1940a) designated USNM 43433 as the “ type ” of Eudendrium rugosum. That name-bearing type material is recorded, correctly, as a holotype in the NMNH online database. Other specimens at the RBCM (BCPM 976-00250-001), labelled “co-type”, constitute paratype ... : Published as part of Calder, Dale R. & Choong, Henry H. C., 2018, Names of hydroids (Cnidaria, Hydrozoa) established by Charles McLean Fraser (1872 - 1946), excluding those from Allan Hancock Expeditions, pp. 1-83 in Zootaxa 4487 (1) on page 24, DOI: 10.11646/zootaxa.4487.1.1, http://zenodo.org/record/1456161 ...